2011
DOI: 10.1002/hon.1012
|View full text |Cite
|
Sign up to set email alerts
|

Repeated transfusions of autologous cytokine‐induced killer cells for treatment of haematological malignancies in elderly patients: a pilot clinical trial

Abstract: The elderly population is susceptible to haematological malignancies, and these elderly patients are intolerant to cytotoxic drugs. Therefore, the exploration of a safe and reliable strategy exclusive of chemotherapy is critical in improving the prognosis of elderly patients with haematological malignancies. We evaluated the safety and the efficacy of autologous cytokine-induced killer (CIK) cells combined with recombinant human interleukin 2 (rhIL-2) in the treatment of haematological malignancies in elderly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…As the next step, Yang et al [37] enrolled 20 patients in a phase I trial. The patients’ age ranged from 57–93 years with a median age of 83 years.…”
Section: Phase I Clinical Studies On Autologous Cik Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the next step, Yang et al [37] enrolled 20 patients in a phase I trial. The patients’ age ranged from 57–93 years with a median age of 83 years.…”
Section: Phase I Clinical Studies On Autologous Cik Cellsmentioning
confidence: 99%
“…Among them, nine were diagnosed with lymphoma, five with MDS, two with multiple myeloma (MM), three with chronic lymphocytic leukemia (CLL) and one with acute myeloid leukemia (AML). Once more, Yang et al [37] combined the CIK cell infusions (2–3 × 10 9 ) with subcutaneous injections of IL-2 (1 mU/day) for 10 consecutive days after each infusion. Six patients received four cycles, and the remaining 14 were administered eight cycles.…”
Section: Phase I Clinical Studies On Autologous Cik Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2012a, b),Laport et al (2011),Introna et al (al. (2012a, b),Laport et al (2011),Introna et al (2007Introna et al ( , 2010,Yang et al (2012Yang et al ( , 2014b,Wang et al al. (2011,Cai et al Wolf et al (1999), Linn et al (2012a, b), Laport et al (2011), Yang et al (2010, 2012), Leemhuis et al (2005), Huang et al (2006), Lu et al (2012), Zhang et al (2012), Olioso et al al.…”
mentioning
confidence: 92%
“…For example, chemotherapeutic agents or glucocorticoids were applied within one week of immune cell transfusion. Overall, fewer than 50 cases with integrated laboratory and clinical data were available for analysis (Yang et al, 2012;Lu et al, 2012;Wang et al, 2013;Sheng et al, 2009). Our five-year practice revealed that this CPC-centered and multidisciplinary collaborative translational approach provided a high-input, low-output model, at least under the current conditions of Chinese hospitals.…”
mentioning
confidence: 99%